IFT20 is required for opsin trafficking and photoreceptor outer segment development - Keady, Brian T. (The American Society for Cell Biology, 2011)
The light-detecting outer segments of vertebrate photoreceptors are cilia. Like other cilia, all materials needed for assembly and maintenance are synthesized in the cell body and transported into the cilium. The highly elaborated nature of the outer segment and its high rate of turnover necessitate unusually high levels of transport into the cilium. In this work, we examine the role of the IFT20 subunit of the intraflagellar transport (IFT) particle in photoreceptor cells. IFT20 was deleted in developing cones by a cone-specific Cre and in mature rods and cones by a tamoxifen-activatable Cre. Loss of IFT20 during cone development leads to opsin accumulation in the inner segment even when the connecting cilium and outer segment are still intact. With time this causes cone cell degeneration. Similarly, deletion of IFT20 in mature rods causes rapid accumulation of rhodopsin in the cell body, where it is concentrated at the Golgi complex. We further show that IFT20, acting both as part of the IFT particle and independent of the particle, binds to rhodopsin and RG-opsin. Since IFT20 dynamically moves between the Golgi complex and the connecting cilium, the current work suggests that rhodopsin and opsins are cargo for IFT transport.